Optimization of sterilization time for carriers’ compost-soil based for production of legume inoculants - Ormeño-Orrillo, Ernesto (1999)
Three soil-compost based carrriers were elaborated and autoclaved by three different treatments of fractionated sterilization in two consecutive days. The efficiency of the sterilization treatments was evaluated monitoring the reduction in bacterial and fungi populations by standard plate count methods. Sterilization of all carriers was possible by the treatment of 45 minutes the first day and 30 minutes the second day.